Uji Efikasi Ekstrak Metanol Daun Torbangun (Plectranthus amboinicus) pada Sel Epitel Kelenjar Susu Manusia MCF-12A - FITRY TAFZI; NURI ANDARWULAN2; PUSPO EDI GIRIWONOB; FITRIYA NUR ANISA DEWID (Fakultas Farmasi Universitas Pancasila, 2017)
Torbangun (Plectranthus amboinicus) is an herbaceous plant that grows in the tropical region. Torbangun can increase breast milk and has antioxidant activity. The objective of this research was to evaluate the antioxidant and cytotoxic activities of methanol extract of torbangun leaves and to identify diff erentially expressed lactation genes upon incubation of MCF-12A human cell epithelial mammary gland with methanolic extract of torbangun leaves. The results showed that the methanolic extract of torbangun leaves had a scavenging activity of DPPH radical with EC50 value of 14.14 μg/ mL. At lower concentration of methanol extracts of torbangun leaves showed no potent cytotoxic eff ect on MCF-12A with IC50 value of 155.24 μg/mL. The methanolic extract of torbangun leaves increased genes expression of prolactin receptor and glucocorticoid receptor in human mammary gland epithelial cells MCF-12A.